A general dynamic model coupled with EFEM and DBM of rolling bearing-rotor system. (1st December 2019) - Li, Yamin; Cao, Hongrui; Tang, Kai
Highlights: The DBM and the EFEM are coupled seamlessly to model the whole system. A variable step numerical integration algorithm is proposed to solve the coupled model. A hybrid bearing - spindle system and a dual rotor - bearing system are analysed. Abstract: Rolling bearing – rotor systems are the key components of many rotational machines. Accurately modeling the bearing – rotor system is of great importance to system design, fault diagnosis, parameter optimization, etc. This paper presents a general dynamic model of rolling bearing – rotor system, which seamlessly couples the rotor's explicit finite element model (EFEM) with a dynamic bearing model (DBM). A variable step numerical integration algorithm combined with the improved Euler method and the central difference method is developed to solve the EFEM and the DBM interactively and simultaneously, thereby the dynamic behavior of the whole system in the time domain can be obtained. A simulation code called DROBOTS is developed based on the proposed model. Experimental validation was carried out on a test rotor supported by two deep groove ball bearings, and a good agreement between the experiment and the simulation shows the accuracy of the proposed model. Finally, a hybrid bearing – spindle system and a dual rotor – bearing system are analyzed by using DROBOTS and some findings are also reported.